PWE-147 Colorectal liver metastasis (CRLM): increasing role of laparoscopic liver resection—a single unit comparative analysis. (28th May 2012) - John, S K P; Rehman, S; Vallance, A; Robinson, S; French, J; Manas, D; White, S
Abstract : Introduction: Laparoscopic liver resection (LLR) is becoming increasingly used to reduce the morbidity of open liver resection The aim of this study was to compare outcomes after LLR with that of open liver resection. Methods: From April 2007 onwards all patients who underwent either left lateral sectionectomy, left hemi-hepatectomy, segmentectomy and non-segmental resection for CRLM were identified from a prospectively maintained HPB database (open and LLR). Those having right hepatectomy were excluded from analysis as there were too few laparoscopic procedures for meaningful analysis. Comparisons between groups were made in terms of complications (graded using the Clavien-Dindo classification), duration of hospital stay and overall survival (OS). Statistical analysis was performed using Fisher Exact test for categorical variables, Mann–Whitney U test for non-parametric continuous variables and overall survival (OS) plotted with Kaplan–Meier curves (SPSS V.19). Results: 78 patients had LLR for various indications (colorectal n=43, non-colorectal n=17, benign n=18). During the same period 94 patients had open equivalent procedures for CRLM (including 4 conversions from a lap procedure). Female patients were more likely to have a LLR compared to open (47% females, 24% males p=0.01). Grade 3 and 4 complications were more seen in the open group (8.5% vs 4.7%), however grade 1 and 2 complications were slightly higher in the laparoscopic group (18.6% vs 17.1%) Median stay was 4 days in LLR group (range 1–23), 7 days (range 3–95) in open group, p<0.001. R1 resections were less during second era of the study in LLR and comparable to the open group. At 3 years 91% of LLR and 72% of open group were alive. OS was similar (p=0.4). Conclusion: Laparoscopic liver resection has shown benefits in terms of lower morbidity in our series when comparing it to equivalent open procedures. Long term follow-up will be needed to see if there is real advantage in OS and outcome. Competing interests: None declared.